Comparison of Conventional and Custom Total Knee Arthroplasty Implants - Dylewicz, Łukasz; Brzoza, Joanna; Bylica, Kinga; Rudzki, Jakub; Warmuz, Wojciech; Wystalska, Ewa; Solarz, Kacper; Czołpińska, Natalia; Kata, Zuzanna; Andrzejewicz, Jakub (Quality in Sport, 2026)
Total knee arthroplasty (TKA) is one of the most successful orthopedic procedures for the treatment of advanced knee osteoarthritis, providing predictable pain relief and functional improvement in a large proportion of patients. Conventional off-the-shelf (OTS) implants remain the standard comparator in studies of customized TKA and are supported by extensive clinical experience, registry-based survivorship data and long-term follow-up analyses. However, concerns regarding anatomical mismatch, variability in native knee alignment and persistent dissatisfaction in a subset of patients have contributed to the development of customized individually made (CIM) implants. The aim of this review was to compare conventional and customized TKA implants with regard to implant design, alignment philosophy, functional outcomes, survivorship and economic considerations. Current evidence suggests that CIM implants may improve anatomical conformity, implant fit and restoration of patient-specific knee geometry. Systematic reviews and meta-analyses have not consistently demonstrated superior clinical outcomes of CIM implants compared with modern OTS systems. Conventional implants continue to show excellent long-term survivorship and remain supported by extensive registry data. Furthermore, many studies evaluating CIM implants are limited by short follow-up duration, methodological heterogeneity and differences in implant design, alignment strategy and comparator groups. In conclusion, CIM implants represent a promising personalized approach in total knee arthroplasty, particularly in terms of anatomical fit and patient-specific reconstruction. Nevertheless, current evidence does not conclusively prove universal superiority over contemporary OTS implants in standard PROMs, revision rates or long-term survivorship, and further long-term comparative studies are required.